Education Planning and Implementation Managemen in MA Al-Azhar, Banjar City - Ahmad Hapidin; Imas Masruroh Imtihanah; Muhibbin Syah; Mohamad Erihadiana; Hisam Ahyani (Sociometry Journal of Social Science, Art and Humanity, 2021)
Today, humans as the most important component of organizational resources receive great attention in the Qur'an, either as individual, social, or human beings as the totality of God's creatures consisting of physical and spiritual elements. Therefore, there is a need for Educational Planning and Implementation Management, especially in private educational institutions. In this study, the researcher took the research locus at Madrasah Aliyah Al Azhar, Banjar City where the formulation of the research problem included, 1) How is the implementation of planning management at the Al Azhar MA, Banjar City?; 2) How is the implementation of education in MA Al Azhar Banjar City?. The method used in this research is using field data sources (field research) with qualitative descriptive analysis. The type of this research is case study research. The results of the study show that, 1) the implementation of planning management at MA Al-Azhar Banjar, in its application using the Collegial Collective work system, where all levels ranging from (principals, vice principals, coaches, teachers and staff) together with committees and staff. foundations have a shared responsibility in advancing their institutions; 2) The person in charge of planning the Education program at MA Al-Azhar Banjar, the Head of Madrasah and the deputy head of the Curriculum sector assisted by all structural position holders; 3) as for the reference for the preparation of the madrasa work program, namely referring to the Vision, Mission, and Objectives of the Al-Azhar Supreme Court, as well as based on the decision of the minister of religion (KMA) and BNSP guidelines; 4) Educational implementation at MA Al-Azhar Banjar, carried out in accordance with government policies regarding PTM in the Covid-19 Pandemic Period, and online and offline (face-to-face) learning processes, while still implementing strict health protocols.